Демографический дайджест - КашницкийИлья Савельевич; БирюковаСветлана Сергеевна (Демографическое обозрение, 2017)
Parr N., J. Li, L. Tickle. A cost of living longer: projections of the effects of prospective mortality improvement on economic support ratios for 14 advanced economies (NCD-RisC), N. R. F. C. A century of trends in adult human height Pal I., J. Waldfogel. The family gap in pay: new evidence for 1967 to 2013 Jakobsson N., A. Kotsadam. Does marriage affect men’s labor market outcomes? A European perspective Gershoff E.T., A. Grogan-Kaylor. Spanking and child outcomes: old controversies and new meta-analyses (NCD-RisC), N.R.F.C. Trends in adult body-mass index in 200 countries from 1975 to 2014: a pooled analysis of 1698 population-based measurement studies with 19.2 million participants Fenge R., B. Scheubel. Pensions and fertility: back to the roots Breschi M., G. Ruiu. Superstitions, religiosity and secularization: an analysis of the periodic oscillations of weddings in Italy